Terapi Bedah Flep dan Cangkok Tulang pada Periodontitis Agresif di Regio Gigi Anterior Mandibula - Levina Mulya; Sri Lelyati C Masulili (Majalah Kedokteran Gigi Indonesia, 2012)
Background: Aggressive periodentitis is a multifactorial disease that usuallyOccurs at a young age with the disease spreading fast and found the bacteria. Commonly aggressive periodontitis associated with hereditary factors and lack of immune system so as to reveal any family history with the same disease, and found savere alveolar bone destruction that may ultimately lead to tooth loss. Aggressive periodontitis and generalized aggressive periodontitis. The development of aggressive periodontitis is difficult to predict, so the mechanical therapy is not sufficient, and required antibiotic therapy or surgical therapy. Aim: the purpose of this case report is to explain the procedures and result of surgical treatment of the flap surgery with bone graft in anterior teeth of the patients with generalized aggressive periodontitis. Case report: Cases one and two with complaints of anterior teeth mobility. On clinical examination teeth mobility two and three degree, absolute pocket depth 4-6 mm. Radiograpic examination bone loss reached one third apical in all region. The diagnosis of both cases in generalized aggressive periodontitis. Treatment: After initial theraphy heve been evaluated, flap surgery with bone graft done in booth cases. Control evaluation after 6 month from surgery, in clinically reduced pocket depth 1-2m and tooth mobility, in radiographically increased bone height and bone fill. Conclusion: Flap surgery with bone graft in generalized aggressive periodontitis can assist periodontal regeneration.